Kestabilan Lokal Titik Ekuilibrium Model Transmisi Penyakit Tuberkulosis - Joko Harianto; Katarina Lodia Tuturop (Department of Mathematics, Hasanuddin University, 2023)
A crucial part of illness prevention over the past few decades has been played by mathematical models. The dynamic system can be used to characterize the TB infection process. For the purpose of developing future prevention strategies, it is crucial to comprehend the effect of vaccination approach on the control of TB. We investigated the impact of vaccination strategies on TB disease transmission through a dynamic model. The model discussed involves logistical population growth. The purpose of this discussion is to analyze the local stability of the equilibrium point of the TB disease transmission model. Numerical simulations are provided to illustrate the theoretical results. The existence and local stability of the model equilibrium point depends on the basic reproduction number analytically. Based on secondary data, the basic reproduction number values are 0.98 and 4.12, respectively. Numerical simulations for these two values support the analysis results obtained. If the basic reproduction number is less than one, then the transmission of TB disease can be eradicated. However, if the basic reproduction number is more than one, the vaccination strategy is not sufficient to control TB transmission.